Student goal orientation, classroom management, parental influences and academic entitlement a case study - Mortel, Rachel Catherine Z.; Koo, Grace S; Salubayba, Teodora M.; Oyzon, Maria Vanessa P. Lusung (Quezon City College of Education, University of the Philippines Diliman, 2021)
The purpose of this sequential explanatory mixed-method case study was to examine and describe Filipino junior high school' academic entitlement and see its relationship with student' goal orientation, teacher's classroom management practices, and parental influence. Data was collected through survey questionnaires and focus group discussions where students, teachers, and parents participated. The data gathered from the survey was analyzed trough means, and the variables were also correlated. Results revealed that the students surveyed had a generally slightly low academic entitlement level and that only a small number of students have high academic entitlement. Also, the students endorsed the mastery approach goal orientation, which had a low negative correlation with academic entitlement. The other goal orientation appeared to have very low negative to no correlation with students' academic entitlement. Teachers' instructional classroom management showed a low positive correlation with academic entitlement. Aspects of parental influence showed no relationship with academic entitlement. However, it had low positive to low negative correlations with the different types of goal orientation. Furthermore, thematic analysis was used for the data collected in the FGDs. This produced a comparison of the characteristics of students then and now, definitions of academic entitlement according to the experiences and effects of academic entitlement, identification of parents, teachers, and school culture as contributors to academic entitlement, and a work in progress when it comes to consistency, communication and consultation, and discipline. A highlight of the study showed that students could use academic entitlement to assert what they rightfully deserve, especially if there is a discrepancy of expectations between the students and the teachers. Thus, the intervention plan must be aligned to what caused academic entitlement.
Thesis
Includes bibliographical references (pages 143-168)
Keywords: Goal (Psychology); Secondary, Education -- Philippines -- Manila Metropolitan Area -- Case studies; Classroom management -- Education (Scondary) -- Philippines -- Manila Metropolitan Area -- Case studies; Junior high school students -- Philippines -- Manila Metropolitan Area -- Attitudes -- Case studies; Parent participation -- Education (Secondary) -- Philippines -- Manila Metropolitan Area -- Case studies